Diversity of lowland hay meadows and pastures in Western and Central Europe. Issue 4 (7th August 2017) - Rodríguez‐Rojo, Maria Pilar; Jiménez‐Alfaro, Borja; Jandt, Ute; Bruelheide, Helge; Rodwell, John S.; Schaminée, Joop H.J.; Perrin, Philip M.; Kącki, Zygmunt; Willner, Wolfgang; Fernández‐González, Federico; Chytrý, Milan
Abstract: Questions: Which are the main vegetation types of lowland hay meadows and pastures in Western and Central Europe? What are the main environmental gradients that drive patterns of species composition? Is it possible to classify these grasslands to phytosociological alliances that reflect management practices? Location: Western and Central Europe (excluding the Alps and Carpathians). Methods: A database of 21 400 vegetation plots of mesic grasslands across Western and Central Europe was compiled. After geographically stratified resampling, semi‐supervised classification based on the K‐means algorithm was applied to assign a subset of plots into 32 a priori association‐level vegetation types and to search for new types within the subset of non‐assigned plots. The vegetation plots assigned into the final vegetation types were submitted to another K‐means classification to show the grouping into higher‐level vegetation types. Results: A total of 36 associations were distinguished in the resampled subset of 8277 vegetation plots and were grouped into four large groups: (1) eutrophic and intensively managed hay meadows and permanent pastures; (2) nutrient‐rich grasslands developed from recently abandoned fields or managed under irregular practices of mowing and manuring; (3) non‐eutrophic lowland and submontane hay meadows; (4) extensively managed pastures and Atlantic grazed hay meadows. A PCoA of the associations of these four groups showed that extensively managed pastures were floristically more similar to non‐eutrophic hay meadows than to permanent intensively managed pastures, which was more obvious in the Atlantic region than in Central Europe. Species composition of the lowland hay meadows was clearly differentiated according to biogeographic sectors. Other floristic differences were related to climate, altitude, soil base status and topography. Conclusions: This analysis challenges the traditional concept of mesic grassland alliances separating hay meadows from pastures. New classification should be based mainly on the differences in management intensity rather than in management practice. Consequently, nutrient‐poor extensive pastures, which currently are not considered in the European Habitats Directive, should receive the same conservation attention as low‐intensive hay meadows, because both types of vegetation can be equally species‐rich and do not differ substantially in floristic composition from each other. Abstract : This paper challenges the traditional concept of mesic grassland alliances separating hay meadows from pastures. They can be classified into four large groups according to the differences in management intensity rather than in management practice. The results provide a basis for the delineation of the habitats of the European Habitats Directive, proposing the inclusion of the nutrient‐poor extensive pastures.